2011
DOI: 10.2478/s11756-011-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of atorvastatin in the chemoprevention of rat mammary carcinogenesis

Abstract: Epidemiological studies indicate that 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, or statins, play a role in inhibition of several human neoplasia including breast cancer. In this study, chemopreventive effects of atorvastatin in N-methyl-N-nitrosourea-induced mammary carcinogenesis in female rats were evaluated. Atorvastatin was administered in the diet at two concentrations: 10 mg/kg (ATOR 10) and 100 mg/kg (ATOR 100). Atorvastatin treatment began 8 days prior to carcinogen administration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…On the other hand, the lower concentration of simvastatin -18 mg/kg in our experiment (equivalent to daily clinical doses) was ineffective in animals. Similarly, significant antitumor effects of atorvastatin (100 mg/kg of diet) administered in the chemoprevention of NMU-induced rat mammary carcinogenesis in our previous study were observed [9]. In our last experiment, hydrophilic rosuvastatin (250 mg/kg of diet) has shown lower chemopreventive activity than lipophilic statins in this model of experimental breast cancer [13].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…On the other hand, the lower concentration of simvastatin -18 mg/kg in our experiment (equivalent to daily clinical doses) was ineffective in animals. Similarly, significant antitumor effects of atorvastatin (100 mg/kg of diet) administered in the chemoprevention of NMU-induced rat mammary carcinogenesis in our previous study were observed [9]. In our last experiment, hydrophilic rosuvastatin (250 mg/kg of diet) has shown lower chemopreventive activity than lipophilic statins in this model of experimental breast cancer [13].…”
Section: Discussionsupporting
confidence: 70%
“…After fluvastatin treatment, expression of Bcl-2 and procaspase-9 were downregulated, cytochrome c (cytosolic extract), Bax and cleaved-caspase-3 protein expression increased [8]. In this context, pro-apoptotic shift of ratio in Bax/Bcl-2 mRNA expression in rat mammary tumor cells caused by atorvastatin in our previous experiment was confirmed [9].…”
mentioning
confidence: 61%
“…Proposed mechanisms for statin-mediated apoptosis include an upregulation of pro-apoptotic protein expression (Bax, Bim) together with decreased anti-apoptotic protein expression (Bcl-2) (Yu et al 2013), or activation of caspase-3, caspase-7, caspase-8 and caspase-9 (Cafforio et al 2005). In our previous experiments there was a pro-apoptotic shift in Bax/Bcl-2 mRNA expression in rat mammary tumour cells after atorvastatin treatment (Kubatka et al 2011a) and pro-apoptotic shift in Bcl-2/Bax protein expression after simvastatin treatment were observed. However, our recent results did not suggest clear pro-apoptotic effects of fluvastatin in rat mammary carcinomas (Kubatka et al 2013).…”
mentioning
confidence: 78%
“…On the other hand, significant anti‐tumour effects of dietary administered lipophilic statins (atorvastatin, simvastatin and fluvastatin) in the chemoprevention of rat mammary carcinogenesis in our previous studies were observed (Kubatka et al . , , ). In our recent experiment, hydrophilic rosuvastatin (250 mg/kg) has shown lower non‐significant anti‐neoplastic activity than lipophilic statins in this model of experimental breast cancer (Kubatka et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation